Finger Vein Minutiae Points Extraction based on Maximum Curvature Points in Image Profile and Finger Print Application Methods - Wan Nourul Akmal Ab Aziz,; Kamaruzzaman Seman; Ismail Abdullah,; M. Norazizi Sham Mohd Sayuti (AENSI Publisher, 2024)
Australian Journal of Basic and Applied Sciences, 7(8): 751-756, 2013 ISSN 1991-8178